2018
DOI: 10.5824/1309-1581.2018.4.008.x
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinde Bilgisayar Oyun Bağımlılığı Düzeyinin Çeşitli Değişkenlere Göre İncelenmesi

Abstract: Bu araştırmanın amacı ortaokul öğrencilerinin bilgisayar oyun bağımlılığı düzeyinin çeşitli değişkenlere göre incelenmesidir. Bu genel amaç doğrultusunda öğrencilerin cinsiyet, sınıf, evde bilgisayar olup olmama durumu ve akademik başarı ortalamaları değişkenlerine göre bilgisayar oyun bağımlılık düzeyleri incelenmiştir. Öğrencilerin bilgisayar oyun bağımlılığını ölçebilmek Horzum, Ayas ve Balta 2008 tarafından geliştirilen çocuklar için “Bilgisayar Oyun Bağımlılığı Ölçeği” kullanılmıştır. Ölçek toplam 21 madd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…As the level of education increases, the level of digital game addiction decreases. Ayhan and Çavuş (2015), Pesen and Şanlı (2018) and Balıkçı (2018) concluded that the level of digital game addiction decreased with increasing levels, while Eryılmaz and Çukurluöz (2018) concluded that there was no significant differentiation according to grade level.…”
Section: Discussionmentioning
confidence: 99%
“…As the level of education increases, the level of digital game addiction decreases. Ayhan and Çavuş (2015), Pesen and Şanlı (2018) and Balıkçı (2018) concluded that the level of digital game addiction decreased with increasing levels, while Eryılmaz and Çukurluöz (2018) concluded that there was no significant differentiation according to grade level.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of computers and the internet in Turkey has caused children to meet computers at an early age, and thus the time spent on computers and the internet has increased [26]. According to the 2019 data of the Turkish Statistical Institute (TUIK), internet use is at 79% among individuals in the 16-74 age group.…”
Section: The Internet Addiction In Turkish Adolescents and Its Contributorsmentioning
confidence: 99%